2021
DOI: 10.3390/cancers13194819
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Levels of Galectin Proteins in Patients with Breast, Colon, and Lung Cancer

Abstract: Galectins are proteins with high-affinity β-galactoside-binding sites that function in a variety of signaling pathways through interactions with glycoproteins. The known contributions of galectins-1, -3, -7, -8, and -9 to angiogenesis, metastasis, cell division, and evasion of immune destruction led us to investigate the circulating levels of these galectins in cancer patients. This study compares galectin concentrations by enzyme-linked immunosorbent assay (ELISA) from each stage of breast, lung, and colon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Our knock out experiments of Gal3 in the stromal cells provided proof-of-principle that a reduction in Gal3 (activity) with its origin in the stromal cells would be beneficial, for example in reducing the chance of persistence of MRD in the induction chemotherapy phase of treatment of BCP-ALL. However, Gal3 is a relatively abundant protein, and ng/mL amounts have been measured in BCP-ALL bone marrow plasma [12], as well as in the serum and plasma of patients with carcinomas (for example, [52]). We note that the knockout of Gal3 in stroma, as studied here, permanently eliminates production of stromal galectin-3, whereas pharmacological galectin-3 inhibition is temporary.…”
Section: Discussionmentioning
confidence: 99%
“…Our knock out experiments of Gal3 in the stromal cells provided proof-of-principle that a reduction in Gal3 (activity) with its origin in the stromal cells would be beneficial, for example in reducing the chance of persistence of MRD in the induction chemotherapy phase of treatment of BCP-ALL. However, Gal3 is a relatively abundant protein, and ng/mL amounts have been measured in BCP-ALL bone marrow plasma [12], as well as in the serum and plasma of patients with carcinomas (for example, [52]). We note that the knockout of Gal3 in stroma, as studied here, permanently eliminates production of stromal galectin-3, whereas pharmacological galectin-3 inhibition is temporary.…”
Section: Discussionmentioning
confidence: 99%
“…It is a potent inducer of cancer cell death in lymphomas and other malignant cell types, such as prostate cancer cells [ 121 ] and colon cancer [ 122 ]. However, Gal-9 is a complex and fragile molecule, with a largely expressed plasma membrane form [ 123 ], an intracellular form [ 124 ] and a circulating soluble form [ 125 ]. The expression and secretion of Gal-9 is promoted by interferon β and γ [ 126 ].…”
Section: Tim-3/gal-9 Signaling Blockade With α/β-Lactosementioning
confidence: 99%
“…The plasticity of galectins and their wide distribution in tissues (not only in the cytoplasm and nuclei but also in the extracellular space) makes them extremely interesting for research but also clinical usability. Many galectins take part in cancers’ invasiveness, and have been related with higher rates of metastases and poorer survival outcome in different cancers [ 11 , 18 ]. Galectin-7 has been linked not only with lung cancer, but also with being highly expressed in epithelial tissues, and related to the regulation of skin homeostasis or keratinocytes proliferation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many galectins take part in cancers’ invasiveness, and have been related with higher rates of metastases and poorer survival outcome in different cancers [ 11 , 18 ]. Galectin-7 has been linked not only with lung cancer, but also with being highly expressed in epithelial tissues, and related to the regulation of skin homeostasis or keratinocytes proliferation [ 18 , 19 ]. Chen et al demonstrated that galectin-7 mRNA was downregulated in human psoriatic lesions and a IL-23-induced psoriasis model that proves the role of the lectin in pathogenesis of psoriasis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%